Livestock - a pathway out of poverty: Interim strategy of the International Livestock Research Institute, 2011-2012 - International Livestock Research Institute (International Livestock Research Institute, 2011)
The interim strategy will serve to guide the institute during a two-year transition period. It will enable ILRI to adopt certain changes in emphasis while positioning the institute for articulation of a new strategy in 2012, when the new Consortium of CGIAR Centres is more firmly established. This delay will ensure that ILRI’s directions are clearly aligned with, and supportive of, the larger strategic framework adopted at the Consortium level as well as the specific challenges of the global livestock sector. It will also permit the incoming director general to participate in a broader range of consultations with partners before adoption of a longer term strategy. This interim strategy for ILRI consists of three parts. The first considers current opportunities and challenges that ILRI must take into account in developing a livestock-research-for-development agenda within the context of the CGIAR reform process and the evolution of the livestock sector worldwide. This suggests ways in which ILRI can best respond to these over the short and medium terms. The second part summarizes lessons ILRI has learned in implementing its current strategy over the last eight years and some of the change in emphasis that this learning implies. The third part briefly describes how the interim strategy will be operationalized over the next two years to position ILRI for the changes expected ahead.